English Learning Activities in Heavy Equipment Engineering Study Program at Olat Maras Community Academy - Musmulyadin, Musmulyadin; Puspitasari, Pipit (Indo-MathEdu Intellectuals Journal, 2023)
Language learning activities are carried out by language educators so that students acquire appropriate language skills after engaging in a learning experience. The nature of English language learning in the Olat Maras Community Academy Heavy Equipment Engineering Study Program is not only focused on delivering the material contained in the semester learning plan but also paying attention to creative aspects, student enthusiasm, and paying attention to the needs of students humanely and democratically. The lack of learning experience for students in general is not only triggered by the difficulty of the content of the subject matter that cannot be understood by students, but also driven by the teaching approach to a learning activity that creates little learning experience for students during learning. The type of research used is qualitative. The instrument of this research is observation and direct interview. Data analysis techniques consist of data reduction, data presentation, and conclusions. The results of data analysis show that creating a learning atmosphere full of student activity must involve cognitive, affective, and psychographic students, such as inviting students to listen, practice, argue, and use learning media sourced from students' own ideas in following their study program.